2007
DOI: 10.1097/mlg.0b013e31806911cc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Purinergic Stimulation on Ciliary Beat Frequency and Chloride Secretion in Sinusitis

Abstract: Mucosal functions, assessed by increase of ciliary activity and ion secretion by purinergic stimulation, and microscopic findings showed gradual but incomplete recovery after 4 weeks of recovery, in contrast to the gross normalization. Purinergic agonists may have beneficial effects on sinusitis by stimulating decreased ciliary motility and chloride secretion in sinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…ATP release from injured cells enhances the inflammatory response through increased synthesis of prostaglandin E 2 (PGE 2 ) [4] via P2X7 receptors [5]. P2X receptor involvement in inflammation also occurs in irritable bowel syndrome [6,7], lung injury and fibrosis [8,9], systemic inflammation [10], arthritis [11], fever [12], and rhinosinusitis [13]. Purinergic signalling in different inflammatory cells involves purinoceptor responses in immune cells (see [14]).…”
Section: Introductionmentioning
confidence: 99%
“…ATP release from injured cells enhances the inflammatory response through increased synthesis of prostaglandin E 2 (PGE 2 ) [4] via P2X7 receptors [5]. P2X receptor involvement in inflammation also occurs in irritable bowel syndrome [6,7], lung injury and fibrosis [8,9], systemic inflammation [10], arthritis [11], fever [12], and rhinosinusitis [13]. Purinergic signalling in different inflammatory cells involves purinoceptor responses in immune cells (see [14]).…”
Section: Introductionmentioning
confidence: 99%
“…These results imply that EMF‐induced homeostasis mechanisms for EMF exposure did not properly compensate. Previous studies showed that CBF in the mucosal explants from the majority of patients with chronic sinusitis was not different from that measured in the explants of healthy tissue 17. However, the increase of CBF by ATP showed differences between the two groups.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies showed that CBF in the mucosal explants from the majority of patients with chronic sinusitis was not different from that measured in the explants of healthy tissue. 17 However, the increase of CBF by ATP showed differences between the two groups. In the normal sinus mucosa group, 100 lM of ATP strongly stimulated CBF with an average increase of 30.1%, whereas the sinusitis group showed only a slight increase of CBF by ATP with a range of 3.2$12.2%.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, two decades ago some studies had reported that exogenous addition of extracellular ATP can improve ciliary beat frequency (CBF) in epithelial cells derived from frog palate and esophagus [ 25 , 26 ]. The modulation of CBF was further shown to occur through activation of purinergic receptors present on the cilium [ 3 , 27 , 28 ]. Consistent with these findings, mutant mice lacking purinergic receptors showed a significant reduction in CBF [ 29 ].…”
Section: Introductionmentioning
confidence: 99%